An intersectional analysis of LncRNAs and mRNAs reveals the potential therapeutic targets of Bi Zhong Xiao Decoction in collagen-induced arthritis rats - Cailin He; Yang Wang; Yuqi Wen; Teng Li; En Hu; Siqing Zeng; Bo Yang; Xingui Xiong (BMC, 2022)
Abstract Background Bi Zhong Xiao decoction (BZXD), a traditional Chinese herbal formula, has been used clinically for many years to treat rheumatoid arthritis (RA). Both clinical and experimental studies have revealed that BZXD is effective in treating RA, but the mechanism remains unclear. In this study, we aimed to explore the mechanism of efficacy of BZXD through transcriptomic analysis of lncRNA and mRNA. Methods The combination method of ultra-high performance liquid chromatography-mass spectrometry/mass spectrometry was used to assess the quality of BZXD. The efficacy of BZXD in treating collagen-induced arthritis (CIA) was evaluated by clinical assessment, weight changes, hematoxylin-eosin and safranin o-fast green staining, and Micro-CT. Arraystar rat lncRNA-mRNA chip technology was used to determine the lncRNA and mRNA expression profiles of the Control, CIA and BZXD groups, and to screen gene expression profiles related to the curative effect of BZXD. A lncRNA-mRNA co-expression network was constructed for the therapeutic efficacy genes. Through GO function and KEGG pathway enrichment analysis, the biological functions and signaling pathways of therapeutic efficacy genes were determined. Based on fold change and functional annotation, key differentially expressed lncRNAs and mRNAs were selected for reverse transcription-quantitative polymerase chain reaction (RT-qPCR) validation. The functions of lncRNAs targeting mRNAs were verified in vitro. Results We demonstrated that BZXD could effectively reverse bone erosion. After BZXD treatment, up to 33 lncRNAs and 107 mRNAs differentially expressed genes were reversely regulated by BZXD. These differentially expressed lncRNAs are mainly involved in the biological process of the immune response and are closely related to the ECM-receptor interaction, MAPK signaling pathway, Focal adhesion, Ras signaling pathway, Antigen processing and presentation, and Chemokine signaling pathway. We identified four lncRNAs (uc.361−, ENSRNOT00000092834, ENSRNOT00000089244, ENSRNOT00000084631) and three mRNAs (Acvr2a, Cbx2, Morc4) as potential therapeutic targets for BZXD and their microarray data consistent with the RT-qPCR. In vitro experiments confirmed that silencing the lncRNAs ENSRNOT00000092834 and ENSRNOT00000084631 reversed the expression of target mRNAs. Conclusions This study elucidates the possible mechanism of BZXD reversing bone erosion in CIA rats from the perspective of lncRNA and mRNA. To provide a basis and direction for further exploration of the mechanism of BZXD in treating RA.